Biomarker clusters differentiate phenotypes of lumbar spine degeneration and low back pain: The Johnston County Osteoarthritis Project. Issue 3 (September 2022) - Goode, Adam P.; Hu, David; George, Steven Z.; Schwartz, Todd A.; Kraus, Virginia B.; Huebner, Janet L.; Cleveland, Rebecca J.; Taylor, Kenneth A.; Jordan, Joanne M.; Golightly, Yvonne M.
Abstract: Objective: Describe the association between biomarkers and lumbar spine degeneration (vertebral osteophytes [OST], facet joint osteoarthritis [FOA], and disc space narrowing [DSN]), for persons with and without low back pain (LBP) and determine whether clusters based on biomarkers differentiate lumbar spine structure with and without LBP. Methods: Using data from the Johnston County Osteoarthritis Project (2006–2010), we measured serum N-cadherin, Keratin-19, Lumican, CXCL6, RANTES, HA, IL-6, BDNF, OPG, and NPY, and urinary CTX-II. Biomarkers were used to group participants using k-means cluster analysis. Logistic regression models were used to compare biomarker clusters. Results: The sample consisted of 731 participants with biospecimens and lumbar spine radiographic data. Three biomarker subgroups were identified: one characterized by structural degenerative changes; another characterized by structural degenerative changes and inflammation, with pain; and a referent cluster with lower levels of biomarkers, pain, and structural degenerative changes. Compared to the referent subgroup, the structural change subgroup was associated with DSN (OR ​= ​1.94, 95% CI 1.30–2.90) and FOA (OR ​= ​1.72, 95% CI 1.12–2.62), and the subgroup with structural degenerative change, inflammation, and pain was associated with OST with LBP (OR ​= ​1.60, 95% CI 1.04–2.46), FOA with LBP (OR ​= ​1.59, 95% CI 1.04–2.45), and LBP (OR ​= ​1.63, 95% CI 1.11–2.41). The subgroup with structural degenerative changes was more likely to have OST (OR ​= ​1.82, 95% CI 1.06–3.13) and less likely to have FOA with LBP (OR ​= ​0.62, 95% CI 0.40–0.96) compared to the group with inflammation and pain. Conclusion: Clustering by biomarkers may assist in differentiating patients for specific clinical interventions aimed at decreasing LBP.